2016
DOI: 10.1371/journal.pone.0165958
|View full text |Cite
|
Sign up to set email alerts
|

Adult Gli2+/–;Gli3Δ699/+ Male and Female Mice Display a Spectrum of Genital Malformation

Abstract: Disorders of sexual development (DSD) encompass a broad spectrum of urogenital malformations and are amongst the most common congenital birth defects. Although key genetic factors such as the hedgehog (Hh) family have been identified, a unifying postnatally viable model displaying the spectrum of male and female urogenital malformations has not yet been reported. Since human cases are diagnosed and treated at various stages postnatally, equivalent mouse models enabling analysis at similar stages are of signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Sex steroid receptors are known to stimulate both Sonic and Indian hedgehog in numerous cell types, including those in the developing genital tubercle. Further, evidence that the hedgehog pathway is downstream of the androgen receptor is supported by findings that Gli2 and Gli3 mutant mouse models, in addition to temporally controlled deletion of Shh between E13.5 and E15.5, cause hypospadias and a urethral phenotype that is strikingly similar to the hypospadias observed in Gli3 XtJ mutants [10,11,52]. It is currently not known whether exogenous androgens could alleviate or bypass these hedgehog-mediated defects.…”
Section: Plos Geneticsmentioning
confidence: 94%
See 2 more Smart Citations
“…Sex steroid receptors are known to stimulate both Sonic and Indian hedgehog in numerous cell types, including those in the developing genital tubercle. Further, evidence that the hedgehog pathway is downstream of the androgen receptor is supported by findings that Gli2 and Gli3 mutant mouse models, in addition to temporally controlled deletion of Shh between E13.5 and E15.5, cause hypospadias and a urethral phenotype that is strikingly similar to the hypospadias observed in Gli3 XtJ mutants [10,11,52]. It is currently not known whether exogenous androgens could alleviate or bypass these hedgehog-mediated defects.…”
Section: Plos Geneticsmentioning
confidence: 94%
“…Each factor has been shown to contribute to male sex differentiation in distinct ways. For example, while mutations in Gli2 alone caused external genitalia defects, compound mutation with Gli1 showed no additional defects, but its combination with Gli3 exhibited more severe defects [5,[9][10][11]. Further, some studies showed that Gli3 is not essential for the development of external genitalia but others found that Gli3 disruption causes significant genital malformations [5,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The urogenital system includes the urinary tract: composed of the kidney, the ureter, the bladder, and the urethra; and the reproductive tract: composed of the testes, the accessory glands, and the external genitalia (EXG). Recently, an increasing number of regulatory genes for EXG development has been reported [13][14][15][16][17]. Thus, possible insights gleaned from comparisons between urogenital organogenesis with other medical topics, such as prostate cancer, is valuable.…”
Section: Hedgehog Signaling and Emi In Urogenital Organogenesismentioning
confidence: 99%
“…We further characterized one HAR, 2xHAR.238, which showed increased activity in the human ortholog relative to the chimpanzee ortholog. 2xHAR.238 is adjacent to Gli2 , a transcriptional effector of Hedgehog signaling ( 12, 2225 ). We found that 2xHAR.238 regulates Leydig cell expression of Gli2 and physically interacts with the Gli2 promoter, indicating that it is a Gli2 enhancer.…”
Section: Introductionmentioning
confidence: 99%